Der Platz der juristischen Fachsprache in der Experten-Laien-Kommunikation - Heutger, Viola (HERMES - Journal of Language and Communication in Business, 2006)
In this commentary, the author outlines possible contributions of a linguistic monitoring especially to the interpretive work of legal experts from the point of view of a lawyer. However, for such a monitoring to be efﬁcient more efforts must be made from the part of the linguists to make clear what the speciﬁc methodological characteristics of a linguistic monitoring consist in. The article sees possible contribution in ﬁelds like interpreting legal texts in more languages like in the EU system, overcoming the differences of legal systems in international legal cooperation, and optimizing national legal texts produced on the basis of community legal texts in order to make them more accessible for national citizens.